Anthropogenic extinction of Pacific land snails: A case study of Rurutu, French Polynesia, with description of eight new species of endodontids (Pulmonata) - Sartori, André F.; Gargominy, Olivier; Fontaine, Benoît (Zootaxa, 2013)
Faunistic surveys are fundamental in the conservation of land mollusks, particularly as a means of achieving accurate es-timates of species richness and levels of extinction of endangered taxa. The family Endodontidae comprises one of the most diverse groups of indigenous land snails of Pacific Islands. Due to anthropogenic degradation of their habitats, most members of the family are now extinct or severely endangered. In Rurutu, French Polynesia, 11 species of Endodontidae were previously described (10 endemics), but only 1 is known to have been extant during the first half of the 20th Century. Extensive collections made in Rurutu in 2003 recovered only empty shells of these 11 species, as well as of an additional 8 endemic species of endodontids not known to previous investigators: Australdonta oheatora sp. nov., A. anneae sp. nov., A. sibleti sp. nov., A. florencei sp. nov., A. pakalolo sp. nov., A. teaae sp. nov., Minidonta boucheti sp. nov. and M. bieleri sp. nov. The radiation of endodontids in Rurutu was thus much larger than previously envisaged. However, we hypothesize that all species of the family are now extinct in the island.